PEMODELAN MESIN JAJA (VENDING MACHINE) DENGAN MENGGUNAKAN OBJECT ORIENTED ANALYSIS AND DESIGN - Kenali, Fitria; Sari, Ayu Kartika (Jurnal Informatika, 2008)
Vending machine is one of hardware that the system was build using an object oriented approach. Almost half of human job related with it, then the development system of automatic machine getting fast to adapt human needed nowdays.Visual Modeling is the process of taking the information from the model and displaying it graphically using standar set of graphical elements. The standard is vital to realizing one of the benefits of visual modeling: communication. Communication between users, developers, analysts, testers, managers and anyone else involved with a project is the primary purpose of  visual modeling. We can use Unified Modeling Language when make visual modeling. UML is industry-standard modeling notation for object-oriented system, and is the premiere platform rapid application development. One of the primary advantages of the object-oriented modeling is the ability  to build components once and then use them over and over again. We can reuse a basic piece of object-oriented design code in desired system.All in all, visual modeling make easy in implementing software of vending machine those it can increase work time efficiency in developing a vending machine system especially, and generally fulfill human need nowdays. Keyword : Vending Machine, Unified Modelling Language